FRI0377 Classification Criteria for Giant Cell Arteritis: Data from Giacta Informing The Need for Revision. (15th July 2016) - Tuckwell, K.; Collinson, N.; Klearman, M.; Dimonaco, S.; Stone, J.H.; ,
Abstract : Background: Classification criteria are often used to standardize the enrollment of patients (pts) in clinical studies. American College of Rheumatology (ACR) classification criteria for giant cell arteritis (GCA) 1 are >25 years old. Advances in diagnosis and clinical understanding of GCA make their relevance to current studies questionable. Objectives: To compare inclusion criteria for the GiACTA (tocilizumab for GCA) study 2 with 1990 ACR GCA classification criteria. Methods: Pts were enrolled into GiACTA according to study inclusion criteria and were evaluated as to whether they met the 1990 ACR classification criteria (Table). Data are from a live database. Results: Of the 251 pts enrolled into GiACTA, 198 (79%) pts met the 1990 ACR classification criteria. The 53 pts who did not fulfill ACR criteria were eligible for GiACTA based on cross-sectional imaging studies and/or polymyalgia rheumatica (PMR) symptoms. In total, 156 (62%) pts had positive temporal artery biopsies (TAB); of these, 24 also had positive imaging findings. The remaining 95 (38%) pts had no TAB or negative TAB; diagnosis of GCA was confirmed by positive findings from large-vessel imaging studies. Positron emission tomography (PET), often coupled with computed tomography (CT), was important in diagnosis. Positive PET/CT findings contributed to GCA diagnosis in 97 (39%) GiACTA pts. CT angiography and magnetic resonance angiography contributed to diagnosis in 14 (6%) and 8 (3%) pts, respectively. New-onset headache, the only GCA symptom in the ACR criteria, was absent in 33% of GiACTA pts. However, other symptoms that often accompany GCA (PMR, scalp tenderness, jaw claudication, ischemia-related vision loss) were present in 62%, 36%, 34%, and 10% of pts, respectively. Conclusions: The 1990 ACR classification criteria for GCA require updating. Cross-sectional imaging, particularly PET/CT, now plays a major role in establishing the diagnosis of GCA. Symptoms in addition to headache merit consideration as part of revised classification criteria. References: Arthritis Rheum 1990;33:1122. Int J Rheumatol 2013;2013:912562. doi: 10.1155/2013/912562. Disclosure of Interest: K. Tuckwell Shareholder of: Roche, Employee of: Roche Products Ltd., N. Collinson Shareholder of: Roche, Employee of: Roche Products Ltd., M. Klearman Shareholder of: Roche, Employee of: Genentech, S. Dimonaco Employee of: Roche Products Ltd., J. Stone Grant/research support from: Roche, Genentech, Consultant for: Roche, Genentech